KUNCI SUKSES PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI JAWA BARAT - Anisatul Auliya (Fakultas Pariwisata Universitas Pancasila, 2020)
The purpose of this research is to find out the keys to success that have been carried out by the community and stakeholders around the Cibuntu Village in West Java during the implementation of community develoments strategy. This research activity was done in the Cibuntu Village Area of ​​Pasawahan Subdistrict - Kuningan District, West Java in October 2019 - January 2020. The method used in this study was a Qualitative Descriptive Method with Accidental Sampling technique process. After doing this research activities it was found that the community development in the village was successful and could be felt by the community all the positive impact of the activity directly. Based on the results from direct surveys in the Cibuntu Village, interviews with indigenous people and stakeholders around Cibuntu Village, the impact of community development activities in Cibuntu Village that can be felt by the community such as : increased economic activity in Cibuntu Village, increased cultural activities, improved facilities and public services, improving the physical condition of the environment the most important is all activities do by involving community participation. Key Worlds : Community Based Tourism, Tourism Village.